Deep necrotising morphea mimicking dermatitis artefacta - Melato, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
The case of a 45-year old woman affected by facial ulcerative dermatitis diagnosed as dermatitis artefacta was reconsidered on the basis of the histological findings, which were consistent with a very unusual type of morphoae. The extraordinary features of this case, which we suggest calling "deep necrotising morphoea", explain the diagnostic pitfall while highlightingthe inadequacy of current classification of morphoea.
Keywords: Adult; Classification; dermatitis; Dermatitis, irritant; dermatologija; Diagnosis; kožne bolezni; Pathology; Scleroderma, circumscribed